The Value of Big Data to the World Economy - Fahmy, Marwa (The Arab Journal of Administration, 2020)
The word represents the new revolution in the world economy. The value and the problems of big data, both, stems from the analytical requirements to make this big data useful and change it from a curse to a blessing. This paper presents the vision of the author of the relationship between big data and their impact on both companies and countries economy. It tries to answer the question “do big data impact economies? And if it does, how does it do it?”.